Contaminantes emergentes en aguas y remediación de suelos con nanopartículas - Álvarez Calvopiña, Mishell Daniela; Molina Maya, Mateo Joel; Recalde Parra, Génesis Andrea (Zenodo, 2021)
RESUMEN Las matrices ambientales de aire, suelo y agua se ven alteradas por contaminantes, por esta razón, es necesario encontrar tecnologías que sean capaces de proporcionar remediación ambiental. En la presente revisión se aborda a los contaminantes emergentes en aguas y el uso de nanopartículas para la remediación de suelos contaminados. Los contaminantes emergentes (CE) son aquellos que aún no se encuentran regulados, pero que pueden representar un peligro actual o futuro para el ecosistema en general. Los contaminantes orgánicos emergentes (COEs) son un grupo de sustancias orgánicas artificiales que no se encuentran en el medio ambiente de forma natural, y su presencia causa daños al ecosistema. Dentro de este grupo se definen tres subgrupos: los productos farmacéuticos y de cuidado personal (PPCPs), los contaminantes orgánicos persistentes (COPs) y las sustancias químicas disruptoras endócrinas (DEs). Se ha planteado el uso de nanomateriales de ingeniería (NMI) como posibles remediadores, dentro de ellos se encuentra las nanopartículas (NP). Estos son materiales cuyo tamaño es menor a los 100 nm y que constan de tres capas: superficial, caparazón y núcleo. Para su fabricación existen dos estrategias principales: de arriba hacia abajo y viceversa. Las NP más utilizadas son aquellas que tienen una base de hierro (ZVI). La remediación de suelos mediante el uso de NP se da a través de tres procesos principales: adsorción, transformación y fotocatálisis; además, se puede hacer uso de tres procesos adicionales como son la absorción, quimiosorción y fisisorción. En este trabajo se considera el uso de NP para la remediación de suelos contaminados con: metales pesados, pesticidas y compuestos orgánicos persistentes. ABSTRACT The environmental matrices of air, soil and water are altered by pollutants, for this reason, it is necessary to find technologies that are capable of providing environmental remediation. This review addresses emerging pollutants in waters and the use of nanoparticles for the remediation of contaminated soils. Emerging pollutants (EC) are those that are not yet regulated, but that may represent a current or future danger to the ecosystem in general. Emerging organic pollutants (EOCs) are a group of man-made organic substances that are not found in the environment naturally, and their presence causes damage to the ecosystem. Within this group, three subgroups are defined: pharmaceutical and personal care products (PPCPs), persistent organic pollutants (POPs) and endocrine disrupting chemicals (DEs). The use of engineering nanomaterials (NMI) has been proposed as possible remedies, among them are nanoparticles (NP). These are materials whose size is less than 100 nm and which consist of three layers: surface, shell and nucleus. For its manufacture there are two main strategies: from top to bottom and vice versa. The most commonly used NPs are those that have an iron base (ZVI). Soil remediation through the use of NP occurs through three main processes: adsorption, transformation and photocatalysis; In addition, three additional processes can be used, such as absorption, chemosorption and physisorption. In this work the use of NP for the remediation of contaminated soils with: heavy metals, pesticides and persistent organic compounds is considered. : {"references": ["Canipari R, Santis L de, Cecconi S. Female fertility and environmental pollution. International Journal of Environmental Research and Public Health. 2020;17(23):1\u201319.", "Bunting SY, Lapworth DJ, Crane EJ, Grima-Olmedo J, Koro\u0161a A, Kuczy\u0144ska A, et al. Emerging organic compounds in European groundwater. Environmental Pollution. 2021;269(115945):1-13.", "Reichert G, Hilgert S, Fuchs S, Azevedo JCR. Emerging contaminants and antibiotic resistance in the different environmental matrices of Latin America. Environmental Pollution. 2019;255.", "Ohoro CR, Adeniji AO, Okoh AI, Okoh OO. Distribution and chemical analysis of pharmaceuticals and personal care products (PPCPs) in the environmental systems: A review. International Journal of Environmental Research and Public Health. 2019;16(17).", "Balderacchi M, Filippini M, Gemitzi A, Kl\u00f6ve B, Petitta M, Trevisan M, et al. Does groundwater protection in Europe require new EU-wide environmental quality standards? Frontiers in Chemistry. 2014;2(JUN):1\u20136.", "Guerra FD, Attia MF, Whitehead DC, Alexis F. Nanotechnology for environmental remediation: Materials and applications. Molecules. 2018;23(7):1\u201323.", "Lapworth DJ, Lopez B, Laabs V, Kozel R, Wolter R, Ward R, et al. Developing a groundwater watch list for substances of emerging concern: A European perspective. Environmental Research Letters. 2019;14(3).", "Chopra S, Kumar D. Ibuprofen as an emerging organic contaminant in environment, distribution and remediation. Heliyon [Internet]. 2020;6(6):e04087. Available from: https://doi.org/10.1016/j.heliyon.2020.e04087", "Al-Farsi RS, Ahmed M, Al-Busaidi A, Choudri BS. Translocation of pharmaceuticals and personal care products (PPCPs) into plant tissues: A review. Emerging Contaminants [Internet]. 2017;3(4):132\u20137. Available from: https://doi.org/10.1016/j.emcon.2018.02.001", "Krasnobaev A, ten Dam G, Boerrigter-Eenling R, Peng F, van Leeuwen SPJ, Morley SA, et al. Legacy and Emerging Persistent Organic Pollutants in Antarctic Benthic Invertebrates near Rothera Point, Western Antarctic Peninsula. Environmental Science and Technology. 2020;54(5):2763\u201371.", "Lofrano G, Libralato G, Meric S, Vaiano V, Sacco O, Venditto V, et al. Occurrence and potential risks of emerging contaminants in water [Internet]. Visible Light Active Structured Photocatalysts for the Removal of Emerging Contaminants. Elsevier Inc.; 2020. 1\u201325. Available from: http://dx.doi.org/10.1016/B978-0-12-818334-2.00001-8", "Akhbarizadeh R, Dobaradaran S, Schmidt TC, Nabipour I, Spitz J. Worldwide bottled water occurrence of emerging contaminants: A review of the recent scientific literature. Journal of Hazardous Materials [Internet]. 2020;392(2020):122271. Available from: https://doi.org/10.1016/j.jhazmat.2020.122271", "Gomes IB, Maillard JY, Sim\u00f5es LC, Sim\u00f5es M. Emerging contaminants affect the microbiome of water systems\u2014strategies for their mitigation. npj Clean Water [Internet]. 2020;3(1). Available from: http://dx.doi.org/10.1038/s41545-020-00086-y", "Pinos V, Esquivel G, Cipriani I, Mora E, Cisneros J, Alvarado A, et al. Emerging Contaminants in Trans-American Waters. Revista Ambiente e Agua [Internet]. 2019;14(6):e2436. Available from: 10.4136/ambi-agua.2436", "Reinoso Carrasco J del C, Serrano Delgado CY, Orellana Cobos DF. Contaminantes emergentes y su impacto en la salud. Rev Fac Cienc M\u00e9d Univ Cuenca. 2017;35(2):55\u20139.", "Chen H, Wang C, Li H, Ma R, Yu Z, Li L, et al. A review of toxicity induced by persistent organic pollutants (POPs) and endocrine-disrupting chemicals (EDCs) in the nematode Caenorhabditis elegans. Journal of Environmental Management [Internet]. 2019;237(February):519\u201325. Available from: https://doi.org/10.1016/j.jenvman.2019.02.102", "Cabrerizo A, Muir DCG, de Silva AO, Wang X, Lamoureux SF, Lafreni\u00e8re MJ. Legacy and Emerging Persistent Organic Pollutants (POPs) in Terrestrial Compartments in the High Arctic: Sorption and Secondary Sources. Environmental Science and Technology. 2018;52(24):14187\u201397.", "Choo G, Wang W, Cho HS, Kim K, Park K, Oh JE. Legacy and emerging persistent organic pollutants in the freshwater system: Relative distribution, contamination trends, and bioaccumulation. Environment International [Internet]. 2020;135(December 2019):105377. Available from: https://doi.org/10.1016/j.envint.2019.105377", "Farr\u00e9 M, Kantiani L, Petrovic M, P\u00e9rez S, Barcel\u00f3 D. Achievements and future trends in the analysis of emerging organic contaminants in environmental samples by mass spectrometry and bioanalytical techniques. Journal of Chromatography A [Internet]. 2012;1259:86\u201399. Available from: http://dx.doi.org/10.1016/j.chroma.2012.07.024", "Real Academia Espa\u00f1ola [REA]. Diccionario [Internet]. 2021. Available from: https://dle.rae.es/diccionario", "Zacharia J. T. Degradation Pathways of Persistent Organic Pollutants (POPs) in the Environment. In: Persistent Organic Pollutants. 2019. p. 17\u201329.", "Vumazonke S, Khamanga SM, Ngqwala NP. Detection of pharmaceutical residues in surface waters of the Eastern Cape Province. International Journal of Environmental Research and Public Health. 2020;17(11):1\u201313.", "Guo W, Pan B, Sakkiah S, Yavas G, Ge W, Zou W, et al. Persistent organic pollutants in food: Contamination sources, health effects and detection methods. International Journal of Environmental Research and Public Health. 2019;16(22):10\u20132.", "Mottier A, Kientz-Bouchart V, Serpentini A, Lebel JM, Jha AN, Costil K. Effects of glyphosate-based herbicides on embryo-larval development and metamorphosis in the Pacific oyster, Crassostrea gigas. Aquatic Toxicology [Internet]. 2013;128\u2013129:67\u201378. Available from: http://dx.doi.org/10.1016/j.aquatox.2012.12.002", "Blaise C, Vasseur P. Algal microplate toxicity test. Small-Scale Freshwater Toxicity Investigations: Volume 1 - Toxicity Test Methods. 2005;1:137\u201379.", "Soto P, Gaete H, Hidalgo ME. Evaluaci\u00f3n de la actividad de la catalasa, peroxidaci\u00f3n lip\u00eddica, clorofila-a y tasa de crecimiento en la alga verde de agua dulce Pseudokirchneriella subcapitata expuesta a cobre y zinc. Latin American Journal of Aquatic Research. 2011;39(2):280\u20135.", "Miner BE, de Meester L, Pfrender ME, Lampert W, Hairston NG. Linking genes to communities and ecosystems: Daphnia as an ecogenomic model. Proceedings of the Royal Society B: Biological Sciences. 2012;279(1735):1873\u201382.", "di Poi C, Costil K, Bouchart V, Halm-Lemeille MP. Toxicity assessment of five emerging pollutants, alone and in binary or ternary mixtures, towards three aquatic organisms. Environmental Science and Pollution Research. 2018;25(7):6122\u201334.", "Programa de las Naciones Unidas para el Medio Ambiente. Convenio de Estocolmo sobre Contaminantes Org\u00e1nicos Persistentes (COP). Climate Change 2013 - The Physical Science Basis [Internet]. 2010;53:1\u201330. Available from: http://ebooks.cambridge.org/ref/id/CBO9781107415324A009%5Cnhttp://arxiv.org/abs/1011.1669%5Cnhttp://dx.doi.org/10.1088/1751-8113/44/8/085201", "European Commission. Regulation (EU) 2019/1021 of the European Parliament and of the Council of 20 June 2019 on persistent organic pollutants (recast). Official Journal of the European Union. 2019;L169(850):45\u201377.", "Khan I, Saeed K, Khan I. Nanoparticles: Properties, applications and toxicities. Arabian Journal of Chemistry [Internet]. 2019;12(7):908\u201331. Available from: http://dx.doi.org/10.1016/j.arabjc.2017.05.011", "Qian Y, Qin C, Chen M, Lin S. Nanotechnology in soil remediation \u2212 applications vs. implications. Ecotoxicology and Environmental Safety [Internet]. 2020;201(May):110815. Available from: https://doi.org/10.1016/j.ecoenv.2020.110815", "Mohajerani A, Burnett L, Smith J v., Kurmus H, Milas J, Arulrajah A, et al. Nanoparticles in construction materials and other applications, and implications of nanoparticle use. Materials. 2019;12(19):1\u201325.", "Cai Z, Zhao X, Duan J, Zhao D, Dang Z, Lin Z. Remediation of soil and groundwater contaminated with organic chemicals using stabilized nanoparticles: Lessons from the past two decades. Frontiers of Environmental Science and Engineering. 2020;14(5):84.", "Das S, Chakraborty J, Chatterjee S, Kumar H. Prospects of biosynthesized nanomaterials for the remediation of organic and inorganic environmental contaminants. Environmental Science: Nano. 2018;5(12):2784\u2013808.", "Bakshi M, Abhilash PC. Nanotechnology for soil remediation: Revitalizing the tarnished resource [Internet]. Nano-Materials as Photocatalysts for Degradation of Environmental Pollutants: Challenges and Possibilities. Elsevier Inc.; 2019. 345\u2013370. Available from: http://dx.doi.org/10.1016/B978-0-12-818598-8.00017-1", "Altieri M a, Nicholls CI. Sustainable Agriculture Reviews [Internet]. Vol. 11, Sustainable Agriculture Reviews. 2012. 1\u201329. Available from: http://link.springer.com/10.1007/978-94-007-5449-2", "O'Carroll D, Sleep B, Krol M, Boparai H, Kocur C. Nanoscale zero valent iron and bimetallic particles for contaminated site remediation. Advances in Water Resources [Internet]. 2013;51:104\u201322. Available from: http://dx.doi.org/10.1016/j.advwatres.2012.02.005", "Huang D, Qin X, Peng Z, Liu Y, Gong X, Zeng G, et al. Nanoscale zero-valent iron assisted phytoremediation of Pb in sediment: Impacts on metal accumulation and antioxidative system of Lolium perenne. Ecotoxicology and Environmental Safety [Internet]. 2018;153:229\u201337. Available from: https://doi.org/10.1016/j.ecoenv.2018.01.060", "V\u00e1zquez-N\u00fa\u00f1ez E, Molina-Guerrero CE, Pe\u00f1a-Castro JM, Fern\u00e1ndez-Luque\u00f1o F, de la Rosa-\u00c1lvarez MG. Use of nanotechnology for the bioremediation of contaminants: A review. Processes. 2020;8(7):1\u201317.", "Song B, Xu P, Chen M, Tang W, Zeng G, Gong J, et al. Using nanomaterials to facilitate the phytoremediation of contaminated soil. Critical Reviews in Environmental Science and Technology [Internet]. 2019;49(9):791\u2013824. Available from: https://doi.org/10.1080/10643389.2018.1558891", "Zhu Y, Xu F, Liu Q, Chen M, Liu X, Wang Y, et al. Nanomaterials and plants: Positive effects, toxicity and the remediation of metal and metalloid pollution in soil. Science of the Total Environment [Internet]. 2019;662:414\u201321. Available from: https://doi.org/10.1016/j.scitotenv.2019.01.234", "Singh J, Lee BK. Effects of Nano-TiO2 particles on bioaccumulation of 133Cs from the contaminated soil by Soybean (Glycine max). Process Safety and Environmental Protection [Internet]. 2018;116:301\u201311. Available from: https://doi.org/10.1016/j.psep.2018.02.016", "Singh J, Lee BK. Influence of nano-TiO2 particles on the bioaccumulation of Cd in soybean plants (Glycine max): A possible mechanism for the removal of Cd from the contaminated soil. Journal of Environmental Management [Internet]. 2016;170:88\u201396. Available from: http://dx.doi.org/10.1016/j.jenvman.2016.01.015", "Puthenveedu H, Pillai S, Kottekottil J. Nano-Phytotechnological Remediation of Endosulfan Using Zero Valent Nanoparticles. Journal of Environmental Protection. 2016;7(April):734\u201344.", "Vittori Antisari L, Carbone S, Bosi S, Gatti A, Dinelli G. Engineered nanoparticles effects in soil-plant system: Basil (Ocimum basilicum L.) study case. Applied Soil Ecology [Internet]. 2018;123(January):551\u201360. Available from: http://dx.doi.org/10.1016/j.apsoil.2018.01.007", "Courtois P, Rorat A, Lemiere S, Guyoneaud R, Attard E, Levard C, et al. Ecotoxicology of silver nanoparticles and their derivatives introduced in soil with or without sewage sludge: A review of effects on microorganisms, plants and animals. Environmental Pollution. 2019;253:578\u201398.", "Ochoa SA, Erosa G, Vega D, Nev\u00e1rez V. Amonio-Oxidasas Bacterianas y Arqueales Involucradas En El Ciclo Del Nitr\u00f3geno. Terra Latinoamericana. 2015;33(3):233\u201345.", "Miralles P, Church TL, Harris AT. Toxicity, uptake, and translocation of engineered nanomaterials in vascular plants. Environmental Science and Technology. 2012;46(17):9224\u201339.", "Ramanathan A. Toxicity of nanoparticles_ challenges and opportunities. Applied Microscopy. 2019;49(1).", "Bahadar H, Maqbool F, Niaz K, Abdollahi M. Toxicity of nanoparticles and an overview of current experimental models. Iranian Biomedical Journal. 2016;20(1):1\u201311.", "Carocci A, Catalano A, Lauria G, Sinicropi MS, Genchi G. Brief History of the Development of the Transfusion Service. How to Recruit Voluntary Donors in the Third World? 2015;238(December):22\u20138."]}